2017
DOI: 10.1166/jnn.2017.13745
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanostructures Containing Atorvastatin Decrease Lipopolysaccharide-Induced Inflammation in Macrophages

Abstract: Atorvastatin, an inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A reductase, is known to exert lipid-lowering, but also anti-inflammatory effects in extra-arterial locations. In order to avoid its toxicity associated with long-term oral treatment, in this study we have proposed novel lipid nanostructures containing atorvastatin to improve its efficiency and bioavailability after local application in periodontitis inflammation therapy. The physico-chemical characterization of the nanostructures was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The results showed a decrease of lipopolysaccharide inducedproinflammatory cytokines Moisei et al 81 Chitosan and hyaluronic acid…”
Section: Liposomes Atorvastatinmentioning
confidence: 96%
See 1 more Smart Citation
“…The results showed a decrease of lipopolysaccharide inducedproinflammatory cytokines Moisei et al 81 Chitosan and hyaluronic acid…”
Section: Liposomes Atorvastatinmentioning
confidence: 96%
“…Moisei et al 81 formulated liposomes packed with atorvastatin and studied the efficacy after their local administration in human macrophages cells culture. The results showed a larger decrease of lipopolysaccharide-induced-proinflammatory cytokines concentration in the cells culture treated with atorvastatin loaded on liposomes [74% inhibition of IL-6, 48% inhibition of Tumor Necrosis Factor (TNF), and 56% inhibition of IL-8] compared to the control group in which atorvastatin alone was administered (54% inhibition of IL-6, 36% inhibition of TNF, and 26% inhibition of IL-8).…”
Section: Local Drug Delivery Systemsmentioning
confidence: 99%
“…In addition to its lipid-lowering effect, another important attribute of atorvastatin (ATV) is its anti-inflammatory properties in extra-arterial sites. Moisei, Craciunescu, Moldovan, Roseanu, and Trif (2017) reported a new formulation of ATV liposomes that increase its bioavailability and efficiency in local treatment of periodontal tissue inflammation. According to biocompatibility testing, the cytotoxicity associated with the nanostructure was not observed in the range of 50-300 µM lipid concentration.…”
Section: Miscellaneous Studies Exploring the Pharmacological Effects Of Liposomal Statinsmentioning
confidence: 99%
“…Comparing free ATV, empty liposomes and ATV liposomal formulation showed that the highest inhibition of tumor necrosis factor-α, interleukin (IL)-6, and IL-8 secretion was observed in the presence of the ATV liposomal formulation. Thus, liposomal formulation may improve the ATV anti-inflammatory effect and this is a promising strategy for local treatment of periodontitis inflammation (Moisei et al, 2017).…”
Section: Miscellaneous Studies Exploring the Pharmacological Effects Of Liposomal Statinsmentioning
confidence: 99%